Limia mandibularis, a new livebearing fish (Cyprinodontiformes: Poeciliidae) from Lake Miragoane, Haiti - Rodriguez-Silva, Rodet; Torres-Pineda, Patricia; Josaphat, James (Zootaxa, 2020)
Limia mandibularis, a new livebearing fish of the family Poeciliidae is described from Lake Miragoane in southwestern Haiti on Hispaniola. The new species differs from all other species in the genus Limia by the presence of a well-developed lower jaw, the absence of preorbital and preopercular pores, and preorbital and preopercular canals forming an open groove each. The description of this new Limia species from Lake Miragoane confirms this lake as an important center of endemism for the genus with a total of nine described species so far.